Struktur Rumah Tangga Dan Perawatan Kesehatan Lansia Di Indonesia - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
ABSTRAK The role of family in elderly care in Indonesia remains feasible solution for both economic and cultural reasons. Rapid socio-economic changes have raised the concerns whether family members can effectively meet the need of elderly care. This study examines the relationship between household structure variables and the use of health services. We seek to learn the household structure characteristics that facilitate or constrain elderly care. If there is no constraint within the family, elderly people living dependently to their children will be less likely to show difference in health care practices as opposed to those living independently. The data for this analysis is drawn from the 1993 Indonesian Socio-Economic Survey. Individuals aged 65 years or above reported to have illness complaints in the past two weeks and remained suffered when the survey was performed are included for the analysis. The findings indicate that the elderly people living dependently with their children or with other families use less health care available outside their homes than those living independently. Keywords: elderly care